COMPARISON BETWEEN EFFECT OF TWO DIFFERENT DOSES OF INTRAVENOUS DEXMEDETOMIDINE IN ATTENUATING HEMODYNAMIC RESPONSE TO LARYNGOSCOPY AND ENDOTRACHEAL INTUBATION IN ELECTIVE GENERAL SURGERIES UNDER GENERAL ANAESTHESIA - KABARA, JYOTI; MEENA, SHRIPHAL; JAIN, PRIYANKA; GAGRANI, VAIBHAV (International Journal of Current Pharmaceutical Research, 2024)
Objective: The process of intubation is a noxious stimuli leading to a period of hemodynamic stress and is accompanied with intense sympathetic activity marked by tachycardia, hypertension and arrythmias. Methods: It was a randomised, prospective, double-blind study. After approval from the ethics committee 60 patients (ASA class 1 and II) were selected randomly, thirty in each group. Group A (n=30) received 0.5 µg/kg of inj. Dexmedetomidine and Group B received 0.75µg/kg of inj. Dexmedetomidine in 20 ml of normal saline as an infusion over 10 min. The patient was induced with inj Fentanyl 1µg/kg, inj. Propofol and inj. Succinylcholine administered and intubated. The primary outcome variables were heart rate and blood pressure at 1, 3, 5, 10, 15 min after intubation. The secondary outcome variables were the effect on the induction dose of propofol and any adverse effect associated with dexmedetomidine. The statistical package used was spss version 22. Results: The hemodynamic responses were attenuated in both groups after laryngoscopy and endotracheal intubation, with statistical significant difference between both groups and better obtundation of hemodynamic response in terms of heart rate, systolic, diastolic and mean arterial pressure at all points of time with dexmedetomidine 0.75µg/kg. Sedation scores were more with dexmedetomidine 0.75µg/kg. No significant side effects were there in both groups. Conclusion: Inj. dexmedetomidine 0.75µg/kg is more effective in attenuating the response to laryngoscopy and endotracheal intubation.